Not open for all: accessibility of open textbooks - Elena Azadbakht (Ubiquity Press, 2021)
In order for open educational resources (OERs) to be truly open to all, they must be accessible to learners with disabilities, including those with visual, auditory, physical and cognitive disabilities. This study sought to determine the accessibility of a randomly selected sample of 355 open textbooks using a custom rubric based upon the World Wide Web Consortium’s (W3C’s) Web Content Accessibility Guidelines (WCAG), version 2.1, primarily at the Levels A and AA. Included books fell into one of four format types: HTML files/websites, PDFs, Microsoft Word documents and EPUBs. The average number of ‘fails’ – instances in which they ran afoul of a rubric category – across the whole sample was 5.93 and the median was 6, out of a total of 14 or 15 categories, depending on the format type. Overall, most of the books did not meet basic accessibility requirements, such as including alternative text for any images, properly coding/tagging any tables and following a logical heading order structure.